POLA PENGAMBILAN KEPUTUSAN KONSUMEN ROKOK - Moechamad Nasir (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2010)
Age, education of consumer and consumer appetitude have the hand in glove relation to brand election smoke by consumer. This matter is shown by calculation by using Chi Square, Kontingensi C and also C Maks. By using Chi Square, age, education and consumer appetitude yield the X2 count that is 46,157; 28,959 and 36,782. So that this matter show the existence of strong relation among age, education, consumer appetite to brand smoke. Calculation of C Maks for the age of, education and appetitude yield 0,50; 0,57 and 0,52. This matter can show big degree of openness of each factor seenly at difference assess the C and C Maks. Pursuant to calculation of difference of C and C Maks in earning value 0,02 for the age of, 0,22 for the education and 0,14 for the appetitude. This means age factor have the strongest relation to purchasing smoke Gudang Garam compared factor of education and appetitude. Pursuant to hypothesizing expressing that “Age, education and appetitude have the hand in glove relation in product purchasing smoke Gudang Garam consisted by various type, for example : Gudang Garam International, Gudang Garam Surya 12, Gudang Garam Surya 16, and Red Gudang Garam is proven by its truth; while hypothesizing expressing dominant factor its influence in election smoke Gudang Garam is age level”, is also proven by its truth.